The effects of teacher deployment policy on curriculum implementation in Tanzania: a case study of selected public secondary schools in a rural district - Machumu, Malima; Mislay, Moshi Amsi (Papers in Education and Development, 2024)
This study investigated the implementation of secondary school teachers' deployment policy, focusing on its effects on curriculum implementation using Selected Rural District experiences. The study aimed to examine the situation and effects of teacher deployment in public secondary schools in a Selected Rural District. Guided by Labour Demand and Supply Theory, the study utilised a qualitative approach and a multiple case study design. Data were collected through face-to-face semi-structured interviews, focus group discussions, and document reviews. Thematic analysis revealed insufficient teacher supply and adverse effects on curriculum implementation, including poor student performance, poor teacher preparations, heavy workloads, minimal classroom engagement, and reliance on lecturing. The recommendations emphasise the need for the government to establish clear policies, guidelines, and strategies for equitable teacher deployment, especially in challenging areas.